The Wild duck - Ibsen, Henrik, 1828-1906.; Ullmann, Liv.; Irons, Jeremy, 1948-; Safron, Henri (Stamford, Conn. : Vestron Video, 1985)
A dramatization of Henrik Ibsen's play of the same title, about a middle class family whose illusions of happiness and comfort are shattered by the arrival of a self-proclaimed truthteller.
VHS format.
Music, Simon Walker ; photography, Peter James ; editor, Don Saunders.
Liv Ullmann, Jeremy Irons, Lucinda Jones.
Keywords: Feature films